Ice Core Analysis Disclose Increased CO2 But No Greenhouse Effect - Lindgren, Mats (European Journal of Applied Sciences, 2023)
European Project for Ice Coring in Antarctica has carefully analyzed Temperature and CO2-concentration during 800.000 years from now. During this period a number of Milankovitch cycles appear. A Milankovitch cycle is a change in the Earth`s symmetrical movements resulting in variations of solar radiation and thus Earth Temperature. Analysis of Temperature and CO2-concentration during a Milankovitch cycle disclose that CO2-concentration during Temperature reduction is much higher than during Temperature increase but that has not affected the Temperature, which means that no Greenhouse effect occurs.